2020
DOI: 10.1371/journal.pone.0231978
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative mass spectrometric analysis of the mouse cerebral cortex after ischemic stroke

Abstract: Ischemic strokes result in the death of brain tissue and a wave of downstream effects, often leading to lifelong disabilities or death. However, the underlying mechanisms of ischemic damage and repair systems remain largely unknown. In order to better understand these mechanisms, TMT-isobaric mass tagging and mass spectrometry were conducted on brain cortex extracts from mice subjected to one hour of middle cerebral artery occlusion (MCAO) and after one hour of reperfusion. In total, 2,690 proteins were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…Several proteomic analyses of AIS using MCAO models have been reported. They were conducted on transient MCAO mouse or rat models and generally focused on the acute phase poststroke.…”
Section: Introductionmentioning
confidence: 99%
“…Several proteomic analyses of AIS using MCAO models have been reported. They were conducted on transient MCAO mouse or rat models and generally focused on the acute phase poststroke.…”
Section: Introductionmentioning
confidence: 99%
“…Ribosomal proteins (RPs) play an important role in the regulation of gene expression and protein synthesis [19]. Elsewhere, an experimental study found that cytoplasmic ribosomes play a role in functional recovery after ischemic stroke [20]. In the present study, the GO and KEGG results revealed that immune response and ribosomes are critical links in the mechanism of female patients with ischemic stroke.…”
Section: Discussionmentioning
confidence: 49%
“…To evaluate the function of the regulated proteins in the ipsilateral hemisphere and their impact on stroke outcome, we assigned the significantly regulated proteins to gene ontology functional categories (GO-term: biological process) using a cut-off for a 2-fold upregulation and for a 0.5-fold downregulation compared to wt bgi. These results show that the regulated proteins were found within the signaling processes commonly involved after ischemic brain injury, such as cell proliferation, cell differentiation, cell growth, cell death, translation, transcription, synaptic plasticity, signal transduction, metabolism, protein transport, vesicle transport, proteolysis, cell adhesion, membrane potential, immune response/inflammation, cytoskeleton organization, and regulation of hydrogen peroxide ( Tables S6–S8 ) [ 33 , 34 , 35 ]. As these processes were affected in all genotypes, the analyses did not allow the identification of a main mechanism for the respective genotypes.…”
Section: Resultsmentioning
confidence: 99%